Optimalisasi Supervisi Kepala Ruangan terhadap Peningkatan Pelayanan Bermutu di Rumah Sakit - Yunita Panjaitan; La Ode Abdul Rahman; Rr. Tutik Sri Hariyati; Yuni Susiana Nur (Journal of Telenursing (JOTING), 2022)
This study aims to determine the application of the innovation optimization program for the supervision of the head of the room to improve quality services at Hospital X Bogor. The method used is a pilot project through problem identification, problem analysis, problem priority setting, Plan of Action (POA), implementation and evaluation. The results showed that there was a decrease in the number of poor abilities and a fairly good increase in the capacity of the head of the room in conducting supervision, each of which was 12 people (37.5%). The results also show differences in abilities before and after the socialization of the optimization of the supervision program. In conclusion, the implementation of the supervision of the head of the room at Hospital X Bogor after the innovation optimization program of supervision can be categorized as quite good and affects increasing the head of the room to carry out supervision. Keywords: Head of Room, Quality Service, Supervision